A Probabilistic Time-Constrained Based Heuristic Path Planning Algorithm in Warehouse Multi-AGV Systems⁎This work was supported by National Nature Science Foundation of China (61803161, 61973125); Natural Science Foundation of Guangdong Province (2018A030310371, 2017A030313385); Science and Technology Planning Project of Guangdong Province (2018B010108001, 2017B090914001, 2017B090901040, 2017B030306017); YangFan Innovative & Enterpreneurial Research Team Project of Guangdong Province (2016YT03G125). Issue 2 (2020) - Lian, Yindong; Xie, Wei; Zhang, Langwen
Abstract: This paper mainly focuses on the path planning algorithm of multi-AGV system in the warehouse environment. We first analyze and model the path network of multiple AGVs based on dynamic stochastic network theory. Then, a probabilistic time constraint is added in the process of the well-known A ⁎ heuristic algorithm, and the solution of the time cost is proposed based on probability theory. Furthermore, a multi-AGV conflict avoidance strategy suitable for heuristic planning algorithms is achieved in combination with queuing mechanism. Finally, numerical simulation experiments of the warehouse multi-AGV system are realized and demonstrate the effectiveness of the proposed algorithm.